Electronic structure-based rate rules for Ḣ ipso addition–elimination reactions on mono-aromatic hydrocarbons with single and double OH/CH3/OCH3/CHO/C2H5 substituents: a systematic theoretical investigation. Issue 36 (9th September 2020) - Pratali Maffei, Luna; Faravelli, Tiziano; Cavallotti, Carlo; Pelucchi, Matteo
Abstract : Systematic theoretical investigation of ipso substitution by H on mono-aromatic hydrocarbons (MAHs), bio-oils components relevant to the pyrolysis and combustion kinetics of MAHs for the prediction of PAHs growth and surrogate fuels formulation. Abstract : The recent interest in bio-oils combustion and the key role of mono-aromatic hydrocarbons (MAHs) in existing kinetic frameworks, both in terms of poly-aromatic hydrocarbons growth and surrogate fuels formulation, motivates the current systematic theoretical investigation of one of the relevant reaction classes in MAHs pyrolysis and oxidation: ipso substitution by hydrogen. State-of-the-art theoretical methods and protocols implemented in automatized computational routines allowed to investigate 14 different potential energy surfaces involving MAHs with hydroxy and methyl single (phenol and toluene) and double ( o -, m -, p -C6 H4 (OH)2, o -, m -, p -CH3 C6 H4 OH, and o -, m -, p -C6 H4 (CH3 )2 ) substituents, providing rate constants for direct implementation in existing kinetic models. The accuracy of the adopted theoretical method was validated by comparison of the computed rate constants with the available literature data. Systematic trends in energy barriers, pre-exponential factors, and temperature dependence of the Arrhenius parameters were found, encouraging the formulation of rate rules for Ḣ ipso substitutions on MAHs. The rules here proposed allow to extrapolate from a reference system the necessary activation energy and pre-exponential factor corrections for a large number of reactions from a limited set of electronic structure calculations. We were able to estimate rate constants for other 63 Ḣ ipso addition–elimination reactions on di-substituted MAHs, reporting in total 75 rate constants for Ḣ ipso substitution reactions o -, m -, p -R′C6 H4 R + Ḣ → C6 H5 R + Ṙ′, with R, R′ = OH/CH3 /OCH3 /CHO/C2 H5, in the 300–2000 K range. Additional calculations performed for validation showed that the proposed rate rules are in excellent agreement with the rate constants calculated using the full computational protocol in the 500–2000 K range, generally with errors below 20%, increasing up to 40% in a few cases. The main results of this work are the successful application of automatized electronic structure calculations for the derivation of accurate rate constants for Ḣ ipso substitution reactions on MAHs, and an efficient and innovative approach for rate rules formulation for this reaction class.